Karakteristik Organoleptik dan Daya Terima Produk Brownies Crispy Berbasis Tepung Daun Kelakai, Tepung Bawang Dayak, Tepung Oatmeal dan Tepung Mocaf - Dewi, Shintia; Mashar, Harlyanti Muthma'innah; Supriyono, Teguh; Mahalia, Lamia Diang (NUTRIASIK: Jurnal Terapan Gizi dan Pangan Fungsional Kesehatan, 2026)
The utilization of local food resources such as kelakai leaves and Dayak onions as functional food ingredients represents an important strategy to enhance nutritional value while reducing dependence on wheat flour. Central Kalimantan has abundant local plant resources that can be developed into innovative food products, including crispy brownies as an alternative functional snack. This study aimed to evaluate the organoleptic quality and acceptability of crispy brownies formulated with a combination of kelakai leaf flour, Dayak onion flour, oatmeal flour, and modified cassava flour (MOCAF). The study employed a Completely Randomized Design (CRD) with three formulation treatments (P1, P2, and P3). Organoleptic and hedonic tests were conducted by 30 semi-trained panelists using parameters of color, aroma, taste, and texture. Data were analyzed descriptively. The results showed that the crispy brownies exhibited a typical brown color, characteristic brownie aroma, moderately sweet taste, and a less crispy texture. Formulation P1 received the highest scores for color and taste, while formulation P2 showed superior aroma and texture. Overall, formulation P2 was the most preferred by the panelists. In conclusion, formulation P2 was identified as the optimal formulation in producing favorable organoleptic quality and the highest level of acceptability.